Should not “beauty and pleasure” be complemented with “cognition and communication”? Reflections upon Denis Dutton’s art instinct: beauty, pleasure and human evolution (Diametros, 2011)
Recenzja książki: Denis Dutton, The Art Instinct: Beauty, Pleasure and Human Evolution,Oxford University Press, Oxford 2009